Toxicity Testing of Three Commonly Used Herbicides on Soil- Dwelling Ant (Family: Formicidae - Odontomachus simillimus) - Zanuri, Siti Hanisah; Khalik, Mohd Zacaery (Borneo Journal of Resource Science and Technology, 2016)
Toxicity evaluation of three commonly used herbicides by public consumer in Kuching district, namely: glyphosate-isopropylamine, triclopyr butotyl and clethodim were conducted against soil-dwelling ants, Odontomachus simillimus. Different concentrations (5, 15, 25, 35, 45, 55 and 65%) of selected herbicides with five replicates for each concentration with addition of one negative control were tested in this study. The ants were treated with 1 μL of herbicides at the thorax and the observations of mortality were recorded within 24 hours. By using probit analysis, LD50 and LD90 values of three selected herbicides were obtained: glyphosateisopropylamine 1.76% and 1.83%, triclopyr butotyl 1.56% and 1.88%, and clethodim 0.47% and 0.94%, respectively. Triclopyr butotyl was found as the most toxic herbicide followed by clethodim and glyphosateisopropylamine based on the study conducted.